2015
DOI: 10.1002/msc.1104
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Experiences of Nurse‐Led Screening for Cardiovascular Risk in Rheumatoid Arthritis

Abstract: When planning future screening programmes for CVD for patients with RA, it is important that the screening consultation is individualized and tailored to patients' needs and their RA. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…Our results may not be generalizable to other practices. However, our findings are consistent with prior studies with much smaller numbers of subjects (11,12). Many patients were not reachable, leading to potential response bias, although the majority of patients who were reachable agreed to participate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results may not be generalizable to other practices. However, our findings are consistent with prior studies with much smaller numbers of subjects (11,12). Many patients were not reachable, leading to potential response bias, although the majority of patients who were reachable agreed to participate.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies reported on patient awareness of the higher CV risk associated with the diagnosis of RA (9,11‐13). Some reports were based on extensive in‐person interviews of a few patient volunteers (11,12). Similar to the results of our study, knowledge of RA as a CV risk factor was reportedly low (less than 50%) in patients and decreased with increasing age (13).…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence from various studies supports the distinct role of the nurse for patients with RA. Nurses have an established role in joint examination, management of comorbidity screening, strengthening of adherence to vaccination regimens, early detection of arthritis, interpretation of laboratory results, and initiation and adjustment of the pharmacological treatment 11 60–68…”
Section: Resultsmentioning
confidence: 99%
“…One RCT examined depression and found non-inferiority of nurse-led care compared with rheumatologist-led care 16. Qualitative studies emphasised that patients valued the opportunity to discuss the wider implications of their condition with a nurse 47–49 67. The TF perceived that addressing these needs includes assessment and identification of psychosocial problems, counselling and referral to other health professionals when needed, which are key components of nursing care, and described in one report of practice experience 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation